PROFIL SENYAWA POLAR TIGA JENIS MINYAK GORENG SELAMA PENGGORENGAN TAHU DAN TEMPE - Titri Siratantri Mastuti; Dedi Fardiaz; Didah Nur Faridah (Jurnal Teknologi dan Industri Pangan, 2019)
The quality of repeatedly used frying oil can be seen from its total polar material (TPM) content. This study aims to determine the influence of different types of oil with different degrees of unsaturation (coco-nut, palm, soybean oil) and foodstuffs with different characteristics (tofu and tempe) to the formation of the polar compounds in repeatedly used frying oil, based on the content of TPM, FFA, BI, FTIR and UV-Vis spectra. Chemical characterization of materials used was done in the first research stage. The second stage was the analysis of the polar compounds of the oil which was used for 3 hours/day for a dried of 15 hours. The results showed that the type of oil and food type affected the levels of TPM with increasing time of frying. The highest level of TPM 19.41±0.13% obtained from combination soybean frying oil-tempeh (15 hours). The FTIR spectrum of the polar fraction from the used frying oil showed a large absorption in area 3600-3200 cm-1 wavelength in which hydroxyl groups indicate the polarity of the frying oil. The rate of in-crease of FFA in all combinations of oil type-tempeh was faster than combination oil type-tofu. Coconut oil-tofu has a slower rate for FFA and browning index. The carbonyl compound in frying oil was showed from peak spectrum absorption at 420 nm.